Riding Globalization: Bancak Salak and The Remaining Identity - Herlinda Suksmawati; Dias Pabyantara; Praja Firdaus Nuryananda (Future Science)
Globalization is believed to be the exogenous driving force that has changed many social and political changes in the last few decades. Deprived of the identity of a socio-political entity, including the people in Indonesia, is a socio-political phenomenon that has become increasingly apparent in recent developments. Supported by increasingly high internet penetration rates, this uprooted culture is even felt in rural areas. But, that does not mean that the local wisdom of Indonesian people can then be lost. Bancakan Salak is one of the cultures of Indonesian people who retain elements of local wisdom. The word